Transformer-Based Sleep Staging Using Continuous Photoplethysmography Signals - Quino, Joseph A. P.; Cardenas, Diego A. C.; Toledo, Marcelo A. F.; Dias, Felipe M.; Ribeiro, Estela; Krieger, José E.; Gutierrez, Marco A. (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2026: Anais do XXVI Simpósio Brasileiro de Computação Aplicada à Saúde, 2026)
Sleep disturbances impair health by disrupting the structure of sleep staging. Although polysomnography is the gold standard, its limited availability has driven photoplethysmography (PPG) alternatives. Transformer models have shown strong performance in sleep staging, though mainly with EEG data. In this work, the TransSleepNet is proposed as a hybrid convolutional–transformer architecture that leverages both approaches, along with a flatline detector to identify and manage invalid PPG segments. It achieved Kappa scores of 0.68 (CFS), 0.61 (ABC), and 0.61 (HomePAP). Results show the flatline detector consistently improves performance, while the proposed architecture matches or outperforms baseline models in generalization datasets.